Siren Songs : Representations of Gender and Sexuality in Opera - Smart, Mary Ann (Book collections on Project MUSE., 2000)
It has long been argued that opera is all about sex. Siren Songs is the first collection of articles devoted to exploring the impact of this sexual obsession, and of the power relations that come with it, on the music, words, and staging of opera. Here a distinguished and diverse group of musicologists, literary critics, and feminist scholars address a wide range of fascinating topics--from Salome's striptease to hysteria to jazz and gender--in Italian, English, German, and French operas from the eighteenth to the twentieth centuries. The authors combine readings of specific scenes with effor.